Design method for out-of-plane motion rejecting structure in 2-DoF large stroke actuators - Wei Bian; Xiaoguang Zhao; Wenshuai Lu; Yijun Yang; Junjie Zhang; Rui You; Fei Xing (Microsystems & Nanoengineering)
Abstract This paper addresses a critical challenge in the design of MEMS actuators: the rejection of out-of-plane motion, specifically along the Z-axis, which can severely impact the precision and performance of these micro-actuation systems. In many MEMS applications, unwanted out-of-plane displacement can lead to reduced accuracy in tasks such as optical steering, micro-manipulation, and scanning applications. In response to these limitations, this paper proposes a novel design technique that effectively rejects Z-axis motion by transforming the motion of the micro stage along the Z-axis into equivalent displacements between pairs of points on cantilevers. These point pairs are founded exhibiting variable common-mode and differential-mode motion characteristics, depending on whether the stage is undergoing in-plane (X/Y) or out-of-plane (Z) displacements. By connecting these point pairs with rods, differential motion between the points in the pairs is suppressed, reducing unwanted out-of-plane motion significantly. We provide a detailed analysis of this design methodology and present a practical application in the form of an electromagnetic large displacement MEMS actuator. This actuator undergoes a complete design-simulation-manufacturing-testing cycle, where the effectiveness of the Z-axis motion rejection structure is systematically evaluated, and compared against traditional designs. Experimental results reveal a significant improvement in performance, with static and dynamic travel ranges reaching ±60 μm and ±400 μm, respectively. Moreover, the Z-axis stiffness was enhanced by 68.5%, which is more than five times the improvement observed in the X/Y axes’ stiffness. These results highlight the potential of the proposed method to provide a robust solution for out-of-plane motion suppression in MEMS actuators, offering improved performance without compromising other critical parameters such as displacement and actuation speed.